Nontraditional Use of TEE to Evaluate Hepatic Vasculature and Guide Surgical Management in Orthotopic Liver Transplantation. (19th June 2019) - Khurmi, Narjeet; Seman, Mitchell; Gaitan, Brantley; Young, Scott; Rosenfeld, David; Giorgakis, Emmanouil; Hewitt, Winston; Mathur, Amit
Abstract : Intraoperative Transesophageal Echocardiography (TEE) during orthotopic liver transplant (OLT) is used to gather real-time information on cardiovascular function and intravascular volume status. We report a case where nonstandard TEE views were used to inspect the hepatic vasculature after allograft implantation. A 29-year-old male with secondary biliary cirrhosis with a MELD score of 20 underwent OLT using a liver from a 21-year-old brain-dead donor. Postreperfusion TEE, using the modified hepatic vein views, confirmed the presence of an inferior vena cava (IVC) suprahepatic anastomotic stenosis and hepatic vein and IVC thrombus resulting in hepatic venous outflow obstruction, allograft congestion, and hemodynamic instability. These nonstandard TEE images established the extent of suprahepatic caval outflow obstruction, in which intraoperative ultrasound was unable to definitively demonstrate. This guided real-time surgical decision-making in the postimplantation phase of the operation—ultimately leading to hepatic vein and IVC thrombectomy and revision of suprahepatic caval anastomosis.